The Comparison of Alternative Income Concepts: A Comment. - Liao, Shu S. (The Accounting Review, 1975)
This article presents comments of the author on the paper "An Intra-Industry Comparison of Alternative Income Concepts and Relative Performance Evaluations," by S.H. Kratchman, R.R. Malcom and R.D. Twark that was published in the October 1974 of the periodical "The Accounting Review." The authors presented an empirical analysis of the impact of basic income concepts on the evaluation of a firm against others in its industry. They concluded that in using net income/total assets as a performance measure, each income concept could be used as a surrogate for other concepts, but in using net income/owners' equity as a performance measure, considerably more caution is needed in using one concept as a surrogate for another. The research methodology used by Kratchman, Malcom and Twark has been examined in three different aspects, that is, statistical methods used, components of net income for the rate of return computation, and the test of impact on rank order changes. Two types of situations to which the rank correlation coefficient is applicable may be distinguished.